PENGARUH VARIASI KONSENTRASI DAN LAMA PERENDAMAN ASAM LAKTA TERHADAP KANDUNGAN GLUKOSA DAN KUALITAS TEPUNG GANYONG (Canna Edualis Kerr ) SEBAGAI PETUNJUK PRAKTIKUM BIOKIMIA - Erika Ayu Desanti; R. Bekti Kiswardianta; Nasrul Rofiah Hidayati (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
This study aims to investigate the influence of concentration and soaking time of lactic acid toward glucose and quality of canna’s starch (Canna Edualis Kerr). The research method using a completelyrandomized design (CRD) with 3x3x3 factorial and three replications. The repetition are K1L1, K1L2,K1L3, K2L1, K2L2, K2L3, K3L1, K3L2, first K3L3. The first factors is variations of concentration (K)include 1%, 1.5%, 2%, the second factor is soaking time (L), there are 60 minutes, 90 minutes, 120minutes. Collecting data by calculating the glucose level using titration method with Na. Organoleptictests include color, odor, texture and level of preference to the 15 panelists using a closed questionnaire.Best organoleptic test are K3L3 treatment (2% of lactic acid concentration with 120 minutes soakingtime) with a total value of 82.5 while the lowest are K3L1 treatment (2% of concentration with a 60minutes of soaking time) with 48.5 of values. Data analysis shows the variation of concentration affect onglucose levels (P = 0.000 <0.05). Soaking time affect on glucose levels (P = 0.000 <0.05) .There are anyinteraction effect of concentration and soaking time on glucose levels. Based on the results showed thatthe highest glucose levels found in K1LI treatment with 1% of lactic acid concentration and 60 minutes ofsoaking time. As for the glucose concentration was lowest for K3L3 treatment with 3% of lactic acidconcentration and 120 minutes of soaking time. The results of this study are used as material preparationBiochemistry lab manual.